Challenges on the road to recovery: Exploring attitudes and experiences of clients in a community-based buprenorphine program in Baltimore City. (June 2019) - Truong, C.; Krawczyk, N.; Dejman, M.; Marshall-Shah, S.; Tormohlen, K.; Agus, D.; Bass, J.
Abstract: Objective: This qualitative study identifies and describes experiences and challenges to retention of individuals with opioid use disorder (OUD) who participated in a low-threshold combined buprenorphine-peer support treatment program in Baltimore. Methods: In-depth semi-structured interviews with staff and former clients of the Project Connections Buprenorphine Program (PCBP) (9 people) and focus group discussions with current and previous clients of PCBP (7 people) were conducted. Content analysis was used to extract themes regarding barriers to enrolling and remaining in, and transitioning from the program. Results: Primary challenges identified by the participants included struggles with cravings and symptoms of withdrawal, comorbid mental health issues, criminal justice system involvement, medication stigma, and conflicts over level of flexibility regarding program requirements and the role of employment. Conclusions: This study identified several obstacles clients face when seeking care through a combined buprenorphine-peer support model. Findings highlight potential programmatic factors that can be improved and additional resources that may support treatment retention rates and better outcomes. Despite challenges, low-threshold and community-based programs can increase access to effective maintenance treatment for OUD, especially among vulnerable populations who may not have access to formal health services. Highlights: Individual client barriers include cravings, withdrawal, and comorbid mental health issues. Treatment was often disrupted by criminal justice system involvement and medication stigma. Participants disagreed on the level of program flexibility and role of employment.